The Strategies of the Use of Green Building Materials Effectively among Contractor in Construction Industry - Lee, Chui Wei; Seow, Ta Wee; Sarpin, Norliana (Research in Management of Technology and Business, 2024)
This research addresses the environmental and health implications of traditional building materials, such as concrete and lead-based paint. Despite the adoption of green building materials, health issues persist, necessitating effective strategies. The study, focused on Johor Bahru, aims to enhance well-being by exploring factors influencing the use of green materials and proposing strategies for their effective implementation among grade 7 contractors. Methodologically, a quantitative approach involved a sample of 135 contractors through a Google Forms survey. Statistical analyses, including ANOVA, revealed non-significant age and education effects but significant racial (p 0.05), suggesting a lesser role in shaping contractors' views in this context. Key findings suggest a consensus on the positive impact of green materials on worker health, indoor air quality, and reduced health incidents. The discussion emphasizes the importance of prioritizing safety, training, and regulatory support. Future work recommendations include assessing the long-term effects of emerging green materials and optimizing their cost-effectiveness and scalability. The study provides vital insights for sustainable and healthy construction.